الدينامية الأسرية كما يدركها الطفل الذي يعاني من التبول أللإرادي - أيت مولود, يسمينة; غازلي, نعيمة (جامعة الوادي - University of Eloued, 2017)
نود من خلال هذه الورقة البحثية فحص دينامية النسق الأسري كما يدركه الطفل الذي يعاني من التبول اللاّإرادي باعتباره فردا يتفاعل ضمنه، وهذا بتطبيق اختبار الادراك الأسري على حالتين عياديتين، مما يسمح لنا بالكشف عن درجةسوء التوظيف للأسرتين اللتين تحضنان هذين الطفلين اللذين لا يتجاوزان من العمر عشر سنوات، ثم ناقشنا النتائج على ضوء بعض الدراسات السابقة والتراث النظري السيكولوجي، ومنه الخروج بجملة من الاقتراحات في سبيل الاستفادة منها لتحقيق التوازن النفسي والاجتماعي للطفل والأسرة ككل. Absract: Through this research, we want to focus on the examination of the family dynamics layout related by the perception of the child who suffers from the involuntary urination since he is considered as an active and dynamic individual; this, by applying the “FAT”, “Family Apperception Test” on two cases, which show the bad living conditions of both families that accommodate the two children under ten years old. Then, we studied the results obtained supported by others studies and the theoretical psychological heritage from which we get some suggestions that could help to realize a psychological and sociological balance for both the child and his family.
دراسة حالة
مقال
Keywords: النسق الأسري - التبول اللاّإرادي–الصحة النفسية للطفل - الطفولة المتأخرة; family layout, involuntary urination, child healthy psychology, late infancy